2017
DOI: 10.1038/bjc.2016.430
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of the PI3K inhibitor BKM120 in patients with advanced or recurrent endometrial carcinoma: a stratified type I–type II study from the GINECO group

Abstract: Backround:Patients with metastatic endometrial carcinoma have a poor prognosis and PIK3CA mutations and amplifications are common in these cancers. This study evaluated the efficacy and safety of the pure PI3K inhibitor BKM120 in advanced or recurrent endometrial carcinoma.Methods:This phase II, multicentre, single-arm, double strata (histological low grade (LG) or high grade (HG)) open-label study enrolled patients with histologically confirmed advanced or recurrent endometrial carcinoma who had received not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Despite the overall disappointing results, the CBR of 24% achieved in this study compares somewhat favorably to recent studies of the other PI3K pathway inhibitors in endometrial cancer. Specifically, a recent phase 2 study of BKM‐120, a pan‐class 1 PI3K inhibitor, in advanced endometrial cancer showed an ORR of 0% and excessive toxicity that necessitated a recruitment hold and dose reduction; 21% of patients discontinued BKM120 for toxicity . Similarly, studies of apitolisib (a dual PI3K/mTOR inhibitor) and pilaralisib (a pan‐class 1 PI3K inhibitor) in advanced endometrial cancer both failed to meet their primary efficacy endpoints (6% ORR in both studies) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the overall disappointing results, the CBR of 24% achieved in this study compares somewhat favorably to recent studies of the other PI3K pathway inhibitors in endometrial cancer. Specifically, a recent phase 2 study of BKM‐120, a pan‐class 1 PI3K inhibitor, in advanced endometrial cancer showed an ORR of 0% and excessive toxicity that necessitated a recruitment hold and dose reduction; 21% of patients discontinued BKM120 for toxicity . Similarly, studies of apitolisib (a dual PI3K/mTOR inhibitor) and pilaralisib (a pan‐class 1 PI3K inhibitor) in advanced endometrial cancer both failed to meet their primary efficacy endpoints (6% ORR in both studies) .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a recent phase 2 study of BKM-120, a pan-class 1 PI3K inhibitor, in advanced endometrial cancer showed an ORR of 0% and excessive toxicity that necessitated a recruitment hold and dose reduction; 21% of patients discontinued BKM120 for toxicity. 11 Similarly, studies of apitolisib (a dual PI3K/ mTOR inhibitor) and pilaralisib (a pan-class 1 PI3K…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more serious problem for clinicians is that either commonly used first-line, or emerging chemotherapeutic drugs cause severe side effects and toxicity [21], which largely limits their clinical use and efficiency. To find safer therapeutic drugs for EC, especially for long-term use, researchers have recently turned to natural anti-tumor drugs containing active plant ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…An example would be the phase 2 study investigating BKM120, a PI3K inhibitor, for endometrial cancer, which was prematurely discontinued because of an unfavorable toxicity profile observed in this specific population. 6 Although BKM120 was established as tolerable with an acceptable safety profile at the estimated maximal tolerated dose of 100 mg/d, 7,8 the same dose resulted in toxicities for women with recurrent endometrial cancer that were not reported in the initial phase 1 trial. Depending on the primary tumor sites and even histological subtypes, the safety profile of BKM120 was found to vary significantly.…”
Section: Introductionmentioning
confidence: 99%